Memory-Load Interference in Syntactic Processing - Gordon, Peter C.; Hendrick, Randall; Levine, William H. (Psychological Science, 2002)
Participants remembered a short set of words while reading syntactically complex sentences (object-extracted clefts) and syntactically simpler sentences (subject-extracted clefts) in a memory-load study. The study also manipulated whether the words in the set and the words in the sentence were of matched or unmatched types (common nouns vs. proper names). Performance in sentence comprehension was worse for complex sentences than for simpler sentences, and this effect was greater when the type of words in the memory load matched the type of words in the sentence. These results indicate that syntactic processing is not modular, instead suggesting that it relies on working memory resources that are used for other nonsyntactic processes. Further, the results indicate that similarity-based interference is an important constraint on information processing that can be overcome to some degree during language comprehension by using the coherence of language to construct integrated representations of meaning.